A "Dança Afro-Brasileira Cênica": experiências pedagógicas em projeto de contraturno escolar - Rocha, Darlene Fabri Ferreira (2022)
The objective of this dissertation is to understand the relationships with knowledge in the teaching and learning process of the "Afro-Brazilian Scenic Dance" (ABSD) through the pedagogical practice of a Physical Education teacher in a dance project in the afternoon of a municipal public school from Vitória/ES. As specific objectives we list: to describe the relationship of the teacher and students with dance and ABSD; to analyze the relationships of Physical Education and dance, as well as of themes that appeared in the daily life of the classes; comprehend how the institution sees the project, the work and the Afro-Brazilian themes developed. The methodological choice was for a case study that led us to a qualitative research with a descriptive character in order to outline the pedagogical practice and understand the subjects' relationships with knowledge in that context. To achieve our goals, studies by Charlot (2000) on the Relation with Knowledge collaborate in the discussion as well as authors of Physical Education whose research brings this theory closer to the area. We consider ABSD as an integral element of ethnic-racial issues and Physical Education, which through body language can promote such discussions through this content. The instruments used for the production of data were observation of the project classes, semi-structured interviews with the teacher and members of the pedagogical team, collective interview with similarities to the focus group with students. The data produced were analyzed by the content analysis method and divided into axes in order to achieve our objectives. The results demonstrate different relationships with dance and ABSD and highlight the relational dimension with knowledge. The content is treated as knowledge and the bodily apprehension evidenced. There are counterpoints and representations that need reflection to avoid the formation or maintenance of stereotypes in relation to the black culture and population. The subjects demonstrate familiarity with ABSD, which we perceive as promoting an anti-racist education.